Limitations and design considerations for donor–acceptor systems in luminescent solar concentrators: the effect of coupling-induced red-edge absorption. (11th May 2016) - MacQueen, Rowan W; Tayebjee, Murad J Y; Webb, James E A; Falber, Alexander; Thordarson, Pall; Schmidt, Timothy W
Abstract: Luminescent solar concentrators (LSCs) use luminescence and waveguiding to concentrate photons within thin dielectric slabs for use in photovoltaic, lighting, and photobioreactor applications. Donor–acceptor systems of organic chromophores are widely used in LSCs to broaden the sunlight absorption range and attempt to reduce loss-inducing reabsorption by the emitting chromophore. We use raytrace simulations across a large parameter space to model the performance of LSCs containing two novel donor–acceptor trimers based on the perylene moiety. We find that under certain conditions, trimers outperform single-dye LSCs as expected. However, at higher concentrations, a slight increase in red-edge absorption by the trimers increases reabsorption and has a deleterious effect on LSC performance. This underscores the large effect that even small changes in the red edge can have, and may discourage the use of donor–acceptor schemes with high interchromophore coupling that promotes red-edge absorption. Finally, we show that for a LSC-PV pair, selecting a PV cell that is well-matched with the LSC emission spectrum has a large effect on the flux gain of the system, and that the systems studied here are well-matched to emerging PV technologies.